2015
DOI: 10.1186/s13071-015-1148-z
|View full text |Cite
|
Sign up to set email alerts
|

Midgut proteome of an argasid tick, Ornithodoros erraticus: a comparison between unfed and engorged females

Abstract: BackgroundThe argasid tick Ornithodoros erraticus is the vector of African swine fever virus and of several Borrelia species that cause human relapsing fever in the Iberian Peninsula. The tick midgut is part of the ectoparasite-host interface and expresses proteins that are vital for the survival of the tick. Midgut proteins are therefore potential targets for drug and/or vaccine design aimed at the development of new strategies for tick control. Thus, the aim of this work was the characterization of the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 57 publications
1
30
0
Order By: Relevance
“…This category is followed by proteins with binding activities representing 37% in both the AM and PM, structural functions (7% in the AM and 8% in the PM), regulators (4% in the AM and PM), transporters (2% in the AM and 3% in the PM), and translation and transcription regulators (3% in the AM and 1% in the PM). These same functional categories have also been identified in other insect midgut proteomes, such as the Glossina palpalis gambiensis tsetse fly [ 20 ] and in ticks Ornithodoros moubata [ 21 ] and Ornithodoros erraticus [ 22 ]. As observed in other proteomics studies [ 23 ], proteins of unknown functions are highly represented, with 35% of all proteins identified in the AM and 32% of those identified in the PM.…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…This category is followed by proteins with binding activities representing 37% in both the AM and PM, structural functions (7% in the AM and 8% in the PM), regulators (4% in the AM and PM), transporters (2% in the AM and 3% in the PM), and translation and transcription regulators (3% in the AM and 1% in the PM). These same functional categories have also been identified in other insect midgut proteomes, such as the Glossina palpalis gambiensis tsetse fly [ 20 ] and in ticks Ornithodoros moubata [ 21 ] and Ornithodoros erraticus [ 22 ]. As observed in other proteomics studies [ 23 ], proteins of unknown functions are highly represented, with 35% of all proteins identified in the AM and 32% of those identified in the PM.…”
Section: Resultsmentioning
confidence: 76%
“…The expression of a large number of HSPs in R. prolixus midgut might be correlated with the arrival of a large amount of warm blood, which induces an increase in the body temperature of the insect. Indeed, members of HSPs were shown to be overexpressed in the midgut of several hematophagous species after a blood meal such as Aedes aegypti [ 26 ], Rhipicephalus microplus [ 27 ], and Ornithodoros erraticus [ 22 ]. In that respect, Hsp70 is the most widely studied HSP as a response to heat and many other stresses [ 24 , 28 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS and RNS appear to be substantial environmental challenges for B. burgdorferi during both blood meal acquisition and during starvation in I. scapularis nymphs, as ROS‐sensitive and RNS‐sensitive B. burgdorferi strains harbouring mutations in antioxidant defence genes show poor survival compared with their wild‐type counterparts (Bourret et al, ; Eggers et al, ; Li et al, ). To the best of our knowledge, the production of ROS and RNS in Ornithodoros ticks has not been reported; however, transcriptomic and proteomic studies have identified a variety of oxidant metabolism and antioxidant defence genes expressed in soft‐bodied ticks that transmit RF Borrelia (Francischetti, Mans, et al, ; Francischetti, Meng, et al, ; Landulfo et al, ; Oleaga, Obolo‐Mvoulouga, Manzano‐Roman, & Perez‐Sanchez, ; Oleaga, Obolo‐Mvoulouga, Manzano‐Roman, & Perez‐Sanchez, ; Oleaga, Obolo‐Mvoulouga, Manzano‐Roman, & Perez‐Sanchez, ).…”
Section: Introductionmentioning
confidence: 99%
“…Several comprehensive protein catalogs describing protein diversity in various tick fluids such as saliva (Madden et al, 2004; Cotté et al, 2014; Radulovic et al, 2014; Tirloni et al, 2014a, 2015) or hemolymph (Gudderra et al, 2002; Stopforth et al, 2010), as well as in midgut during feeding (Schwarz et al, 2014; Oleaga et al, 2015), have been compiled, vital to understanding mechanisms implicated in different biological processes such as tick feeding or tick immunity.…”
Section: Introductionmentioning
confidence: 99%